2010
DOI: 10.1186/1471-2431-10-5
|View full text |Cite
|
Sign up to set email alerts
|

Control of hyperglycaemia in paediatric intensive care (CHiP): study protocol

Abstract: BackgroundThere is increasing evidence that tight blood glucose (BG) control improves outcomes in critically ill adults. Children show similar hyperglycaemic responses to surgery or critical illness. However it is not known whether tight control will benefit children given maturational differences and different disease spectrum.Methods/DesignThe study is an randomised open trial with two parallel groups to assess whether, for children undergoing intensive care in the UK aged ≤ 16 years who are ventilated, have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 54 publications
0
22
0
3
Order By: Relevance
“…The Control of Hyperglycemia in Pediatric Intensive Care trial in the United Kingdom aims to study the impact of TGC on numbers of days alive and freed of ventilator support at 30 days in 1500 critically ill children who are mechanically ventilated and on vasoactive infusions. 101 The Safe Pediatric Euglycemia in Cardiac Surgery study is examining the impact of TGC in reducing nosocomial infections and improving cardiac index at 24 hours following cardiac surgery using a continuous glucose monitoring system in 980 children.…”
Section: Tight Glucose Control In Critical Illnessmentioning
confidence: 99%
“…The Control of Hyperglycemia in Pediatric Intensive Care trial in the United Kingdom aims to study the impact of TGC on numbers of days alive and freed of ventilator support at 30 days in 1500 critically ill children who are mechanically ventilated and on vasoactive infusions. 101 The Safe Pediatric Euglycemia in Cardiac Surgery study is examining the impact of TGC in reducing nosocomial infections and improving cardiac index at 24 hours following cardiac surgery using a continuous glucose monitoring system in 980 children.…”
Section: Tight Glucose Control In Critical Illnessmentioning
confidence: 99%
“…Several investigators have therefore used surrogate outcome measures as the primary outcome. For example, the Safe Paediatric Euglycaemia after Cardiac Surgery (SPECS) study and CHiP investigators used healthcare-associated infections and ventilator-free days as primary outcome measures, respectively44 45; the Trial of Drotrecogin Alfa in Children (RESOLVE) study used a composite outcome measure called ‘composite time to complete organ failure resolution’46 and Transfusion Requirements in PICU (TRIPICU) study used new or progressive multiple-organ dysfunction syndrome 47. While this strategy may be valid and acceptable in some trials, widespread use of proxy short-term outcome measures is perhaps fraught with danger.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…5,6 There are two methods of insulin therapy for hyperglycemic patients due to organ dysfunctions; strict and standard therapy. 13,20 A previous study has showed a low incidence of hypoglycemia with the strict insulin therapy. 13 Therefore, we recommend the strict insulin therapy for hyperglycemia caused by MODS in children requiring intensive care.…”
Section: Discussionmentioning
confidence: 99%